ASSESSMENT OF MICRONUTRIENT ADEQUACY IN OBESE PATIENTS ON EXCLUSIVE ENTERAL NUTRITION IN THE ICU OF A HOSPITAL IN THE NORTHWEST REGION OF THE STATE OF ESPÍRITO SANTO: A RETROSPECTIVE STUDY - Zache Radinz, Bianca; Lopes Silva, Jackelyne; Folador Frederico, Rafael; Nascimento Ronchi, Silas; Lima Garcez, Michelle; Chiepe, Letícia; Rodrigues de Morais Viana, Eduarda Cristina; Bellettini-Santos, Tatiani (UNESC em Revista, 2025)
Critically ill obese patients are at high risk of nutritional deficiencies due to the hypermetabolic state and oxidative stress, which can compromise their recovery. This study aimed to analyze the adequacy of micronutrients in obese patients according to the Body Mass Index (BMI) admitted to an Intensive Care Unit (ICU), who were receiving exclusive enteral nutrition. Data were collected from electronic medical records and a digital database. Micronutrient intakes were assessed based on the Dietary Reference Intakes (DRIs). The study included 46 patients admitted to the ICU, with a median age of 67 years (interquartile range, 58-76 years), and 63% of the patients were male. The leading cause of hospitalization was respiratory disease (60.9%). Data analysis revealed that 12 micronutrients presented levels below the recommended levels, including sodium, calcium, potassium, chloride, magnesium, folic acid, pyridoxine, copper, vitamin A, vitamin D, pantothenic acid and chromium with percentages of 89.1%, 71.9%, 100%, 100%, 78.3%, 95.7%, 41.3%, 63%, 50%, 60.9%, 71.7 and 60.9%, respectively. No nutrient exceeded the tolerable upper intake limit. The findings of this study indicate that exclusive enteral nutrition, as administered, did not guarantee nutritional adequacy for this population, highlighting the need for adjustments in dietary prescriptions. In addition, the scarcity of specific guidelines for critically ill obese patients reinforces the importance of further research to support more precise recommendations on micronutrient administration in this population. Keywords: Obesity, Intensive Care Unit, Micronutrient, Enteral nutrition, Nutritional deficiency.